2016
DOI: 10.1007/s00436-016-4909-5
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis spp. in sheep and goats: frequency of infection and species identification by morphological, ultrastructural, and molecular tests in Bahia, Brazil

Abstract: Sarcocystis spp. are cyst-forming coccidia that infect numerous animals species, including several livestock species. Despite the importance of sheep and goat production in Brazil, little it is known about the Sarcocystis species that infect small ruminants in the country and their potential impact on meat condemnation due to the presence of macroscopic cysts of the parasite. The aims of the present study were to determine the frequency of infection by Sarcocystis spp. in goats and sheep intended for human con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…Bittencourt et al. () examined 53 sheep and 270 goat's samples and found a lower prevalence in sheep (35.8 and 50.7%, respectively). In most of the published studies concerning Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bittencourt et al. () examined 53 sheep and 270 goat's samples and found a lower prevalence in sheep (35.8 and 50.7%, respectively). In most of the published studies concerning Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the published studies concerning Sarcocystis spp. in sheep, high prevalence was reported, reaching 95.8% by light microscopy (Bittencourt et al., ). Two surveys were conducted in Baghdad district (Iraq) and Khorasan province (Iran), showing that all examined sheep samples (100 and 160 isolates, respectively) had microscopic Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, water buffalo can also serve as an intermediated host for S. cruzi (27,28). In Iran, there are many articles confirmed that the predominant species of Sarcocystis in cattle is S. cruzi (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection for identification of macroscopic cysts of Sarcocystis spp. in the tongue, esophagus, and hearts of animals is the preferred method for detection of sarcocystosis in animal carcasses (Bittencourt et al., ). Some species produce only microscopic cysts that cannot be observed by visual inspection.…”
Section: Helminthsmentioning
confidence: 99%